2021
DOI: 10.1016/j.jtcvs.2020.02.115
|View full text |Cite
|
Sign up to set email alerts
|

Commentary: Cracking the code for chronic aortic dissection

Abstract: Remodeling is limited by persistent false lumen perfusion after chronic dissection TEVAR. CENTRAL MESSAGEStent-assisted balloon dilatation may be an important adjunct to true lumen thoracic endovascular aortic repair in select patients with chronic distal aortic dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Continued patency of the false lumen, particularly a partially thrombosed false lumen, has been demonstrated as a major predictor of aortic enlargement after aortic dissection, and our goal was to encourage true lumen expansion and reduce the incidence of repeat thoracoabdominal open or endovascular procedures. 10,15 In this study, two-thirds of patients had chronic thoracoabdominal aortic dissection, and we demonstrated an increase in false lumen thrombosis and an improvement in thoracoabdominal aortic remodeling, suggesting that in addition to the acute phase, a composite stenting technique combining thoracic stent grafts with a distal thoracoabdominal bare metal extension stent technique may encourage distal aortic remodeling in the chronic phase of aortic dissection. The use of the bare dissection stent as an adjunct to descending TEVAR in the setting of chronic dissection may also prevent the occurrence of distal malperfusion secondary to distal stent induced new entry tears.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Continued patency of the false lumen, particularly a partially thrombosed false lumen, has been demonstrated as a major predictor of aortic enlargement after aortic dissection, and our goal was to encourage true lumen expansion and reduce the incidence of repeat thoracoabdominal open or endovascular procedures. 10,15 In this study, two-thirds of patients had chronic thoracoabdominal aortic dissection, and we demonstrated an increase in false lumen thrombosis and an improvement in thoracoabdominal aortic remodeling, suggesting that in addition to the acute phase, a composite stenting technique combining thoracic stent grafts with a distal thoracoabdominal bare metal extension stent technique may encourage distal aortic remodeling in the chronic phase of aortic dissection. The use of the bare dissection stent as an adjunct to descending TEVAR in the setting of chronic dissection may also prevent the occurrence of distal malperfusion secondary to distal stent induced new entry tears.…”
Section: Discussionmentioning
confidence: 60%
“…Given the low radial force of the Zenith Dissection Endovascular Stent, it might be expected that there would be little effect in re-expanding the true lumen against a chronically thickened intimal flap. Faure and colleagues 7 and others 15 have had success with balloon fracturing the chronic flap after deployment of the PETTICOAT stent. This approach also required the stenting of visceral arteries and iliac arteries in more than half of the patient cohort.…”
Section: Discussionmentioning
confidence: 99%